Hubungan kehamilan gemeli dengan kejadian berat badan lahir rendah (BBLR) di RSUD bangkinang kabupaten kampar - Herlena, Herlena; Apriyanti, Fitri; Syahda, Syukrianti (Evidence Midwifery Journal, 2024)
The Infant Mortality Rate (IMR) is the first indicator in determining a child's health status as a reflection of the health status and basic needs of society. One of the causes of high infant mortality rates is low birth weight (LBW). Low Birth Weight (LBW) is a low birth weight baby born with a body weight of less than 2500 grams. LBW is a health problem that needs to be treated seriously because LBW contributes to neonatal death. Babies with low birth weight are 20 times more likely to die than normal babies. The aim of the research is to analyze the relationship between happy pregnancies and the incidence of low body weight (LBW) at Bangkinang District Hospital in 2022. The type of research is analytical research with a case control design. The research was conducted in August 2023 with a total of 62 respondents (babies who experienced low birth weight) and 62 controls (babies who did not experience low birth weight) using random sampling techniques. Data collection uses a checklist sheet. The data analysis used was univariate and bivariate analysis with the Chi Square test. The results of univariate analysis showed that 52 respondents (46.5%) had uneventful pregnancies. The results of the Chi Square test show a relationship between LBW pregnancies and the incidence of low birth weight (LBW) (p value = 0.002) at Bangkinang District Hospital in 2022. The suggestion of this research is to minimize the incidence of LBW and improve health services even better by providing counseling to pregnant women to prevent the occurrence of LBW in newborn babies